2010
DOI: 10.1038/ijo.2010.53
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and biochemical features of obesity are associated with mineralization genes’ polymorphisms

Abstract: Background: Ectonucleotide pyrophosphatase/phosphodiesterase 1 (ENPP1) was recently extensively studied as a candidate gene for obesity phenotypes. As the human homologue of the mouse progressive ankylosis (ANKH) and alkaline phosphatase (ALPL) are known functional partners of ENPP1 in bone mineralization, we hypothesized that these genes may also be jointly involved in determining obesity features. Aim: To examine the effects of the three genes, possible gene-sex and gene-gene interactions on variability of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 58 publications
1
19
0
Order By: Relevance
“…31 Lastly, in humans, a recent study demonstrated that polymorphisms in the tissue-non-specific ALP gene are associated with body fat distribution. 32 Intracellular lipid accumulation and ALP activity were only measured at baseline and on day 12 of the differentiation period. The latter represents a time point at which all the proteins that are characteristic of mature adipocytes are already being expressed.…”
Section: Discussionmentioning
confidence: 99%
“…31 Lastly, in humans, a recent study demonstrated that polymorphisms in the tissue-non-specific ALP gene are associated with body fat distribution. 32 Intracellular lipid accumulation and ALP activity were only measured at baseline and on day 12 of the differentiation period. The latter represents a time point at which all the proteins that are characteristic of mature adipocytes are already being expressed.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis was applied to evaluate the magnitude and relative importance of the various familial sources (including the additive genetic component and heritability) on their variability. Application of this method was previously described by us elsewhere [37,38]. Briefly, the maximum likelihood ratio test (LRT) was used to estimate the relative contribution of the various familial sources on the phenotype variation: V AD , V SP , V HS , and V SIB -variance components attributable to additive genetic factors, as well as the common environment shared by spouses, household members, and siblings.…”
Section: Statistical and Quantitative Genetic Analysismentioning
confidence: 99%
“…To test the association between ROR2 polymorphisms and the study phenotypes, we carried out the pedigreebased disequilibrium test (PDT) [38,39] as implemented in the MAN-9 package. PDT examines the association between the marker genotypes and the quantitative phenotype variation and exploits the complete pedigree data, including the non-genotyped pedigree members.…”
Section: Statistical and Quantitative Genetic Analysismentioning
confidence: 99%
See 2 more Smart Citations